Hướng dẫn trả lời:
a) `1/2x^2 - 3/2y^2`
`= (1/sqrt2x)^2 - (sqrt{3/2}y)^2`
`= (1/sqrt2x + sqrt{3/2}y)cdot(1/sqrt2x - sqrt{3/2}y)`
Giải thích:
Áp dụng HĐT hiệu hai bình phương `A^2 - B^2 = (A + B)cdot(A - B)`
b) `3/4x^2y^2 - 4y^4`
`= y^2cdot(3/4x^2 - 4y^2)`
`= y^2cdot[(sqrt3/2x)^2 - (2y)^2]`
`= y^2cdot(sqrt3/2x + 2y)cdot(sqrt3/2x - 2y)`
Giải thích:
Áp dụng HĐT `A^2 - B^2 = (A + B)cdot(A - B)`
Đáp án:
a) `= (1/sqrt2x + sqrt{3/2}y)cdot(1/sqrt2x - sqrt{3/2}y)`
b) `= y^2cdot(sqrt3/2x + 2y)cdot(sqrt3/2x - 2y)`